Social Impacts of Coastal Resource Depletion on Fishermen Communities in Bantaeng, South Sulawesi - Faizal, Muhammad; Nasrullah, Nasrullah; Mustari, Mustari (Journal Social Civilecial, 2024)
The paper investigates the social consequences of coastal resource depletion through studies on economic troubles and adaptation methods alongside changes within fishing communities of Bantaeng located in South Sulawesi. The investigation focuses on how diminishing fish stocks limits fishermen’s economic viability alongside affected traditional knowledge transfer and impacts fishing community solidarity. Resource depletion exhibits very powerful negative effects on income yet the community now seeks additional sources of revenue by embracing seaweed production and small-farm cultivation. Social interactions in the community have shown both signs of detachment and strengthening because individuals work to obtain resources while others start working together on collective projects. Gender conceptions have undergone transformations according to this study since women now generate economic benefits rather than men do. The research demonstrates how young people leave rural areas for urban destinations because coastal fishing shows declining opportunities which will worsen traditional fishing in the future. The research findings contribute to advancing small-scale fisheries discourse because they concentrate on sociological aspects of adaptation and advise that place-based community-level strategies should serve as main pillars for fisheries policy. This study demonstrates that the social aspect must be integrated for long-term sustainability in coastal resource management to benefit communities.